Adherence of Type 2 Diabetic Patients to Self-Care Activity: Tertiary Care Setting in Saudi Arabia - Ali Hassan Alhaiti; Mohammed Senitan; Wireen Leila T. Dator; Chandrakala Sankarapandian; Nadiah Abdulaziz Baghdadi; Linda Katherine JONES; Cliff Da Costa; George Binh Lenon (Journal of Diabetes Research)
Aim. To analyse the prevalence of self-care practices in T2D patients in KSA. Methods. The study was conducted in King Fahad Medical City (KFMC) in Saudi Arabia, and 385 patients were selected as samples. Data were collected using the Summary of Diabetes Self-Care Activities-Arabic (SDSCA) and consisted of 14 items related to self-care activities of T2D patients related to management and control of disease and four other aspects related to education and advice from healthcare members regarding management of T2D. Results. The self-care attributes including adherence to medication commitment activities (M=6.13, SD=1.25) were the most practised of all the domains. Glucose monitoring (M=4.15, SD=2.42) and foot care (M=3.28, SD=1.69) were at an average level, and adherence to the diet plan and exercise was found to be at a poor level (M=2.57, SD=1.73 and M=2.13, SD=2.00) respectively. About 179 patients (74.3%) were found to be advised to follow a low-fat eating plan, and only 89 patients (36.9%) had received information concerning fruits and vegetables in their diet. More than 90% patients were found to be advised to strictly carry out exercise and blood sugar monitoring. Conclusion. It was found that adherence to self-care activities including diet, exercise, and foot care was relatively poor while intake of medication was strictly followed. The education provided by healthcare providers related to self-management attributes was found to be significant and had positive effects on the overall health and well-being of T2D patients.